Efficacy of Erector Spinae Nerve Block for Pain Control After Spinal Surgeries: An Updated Systematic Review and Meta-Analysis - Duan, Mingda; Xu, Yuhai; Fu, Qiang (Frontiers in Surgery, 2022)
Background: Erector spinae plane block (ESPB), as a regional anaesthesia modality, is gaining interest and has been used in abdominal, thoracic and breast surgeries. The evidence on the efficacy of this block in spinal surgeries is equivocal. Recently published reviews on this issue have concerning limitations in methodology. Methods: A systematic search was conducted using the PubMed, Scopus, Embase and Cochrane Central Register of Controlled Trials (CENTRAL). Randomized controlled trials (RCTs) that were done in patients undergoing spinal surgery and had compared outcomes of interest among those that received ESPB and those with no block/placebo were considered for inclusion. Statistical analysis was performed using STATA software. GRADE assessment was done for the quality of pooled evidence. Results: A total of 13 studies were included. Patients receiving ESPB had significantly reduced total opioid use (Standardized mean difference, SMD -2.76, 95% CI: -3.69, -1.82), need for rescue analgesia (Relative risk, RR 0.38, 95% CI: 0.22, 0.66) and amount of rescue analgesia (SMD -5.08, 95% CI: -7.95, -2.21). Patients receiving ESPB reported comparatively lesser pain score at 1 hour (WMD -1.62, 95% CI: -2.55, -0.69), 6 hours (WMD -1.10, 95% CI: -1.45, -0.75), 12 hours (WMD -0.78, 95% CI: -1.23, -0.32) and 24 hours (WMD -0.54, 95% CI: -0.83, -0.25) post-operatively. The risk of postoperative nausea and vomiting (PONV) (RR 0.32, 95% CI: 0.19, 0.54) was lower in those receiving ESPB. There were no differences in the duration of surgery, intra-operative blood loss and length of hospital stay between the two groups. The quality of pooled findings was judged to be low to moderate. Conclusions: ESPB may be effective in patients with spinal surgery in reducing post-operative pain as well as need for rescue analgesic and total opioid use. In view of the low to moderate quality of evidence, more trials are needed to confirm these findings.